Expressão de Indoleamina 2,3 Dioxigenase (IDO) em células T24 de carcinoma de bexiga urinária submetidas à hipóxia: correlação com Fator de Crescimento Endotelial Vascular (VEGF) - Cesário, Jonas Magno dos Santos (2015)
The urinary bladder cancer is the most common malignancy of the urinary system and for his growth and progression, angiogenesis is necessary. A indoleamine 2,3-dioxygenase (IDO), a molecule known for its immunomodulatory properties arises as a potential modulator of angiogenesis. Its expression is associated with pro-angiogenic factors in different types of cancer, but in bladder cancer has not yet been explored. The aim of this study was to analyze IDO expression in T24 cells of bladder carcinoma in situation of hypoxia in order to correlate it with angiogenesis-inducing factors. T24 cells were subjected to hypoxia by AnaeroGen product during four periods of incubation (1 h, 8 h, 24 h and 48 h). Real time RT-PCR was performed to analyze the expression of VEGF, HIF and IDO. Cells without hypoxia were used as controls. As a second step, the cells were treated with the IDO inhibitor (1-methyl tryptophan) and subjected to hypoxia or not for the evaluation of VEGF expression. In addition, HUVEC cells were treated with the IDO inhibitor to assess cell viability. In "in vivo" step, Balb/c nude received T24 cells under the kidney capsule for the establishment of a model that would allow assessment of tumor neovasculature (30 days). The characterization of neovascularization was performed by immunohistochemistry. The expression of VEGF was significantly increased over the incubation periods, and time-dependent. But the expression of HIF and IDO did not change significantly. However, there was a positive correlation between HIF and IDO (correlation coefficient 0.615, Spearman). Treatment with the IDO inhibitor significantly decreased VEGF expression in T24 cells subjected to hypoxia, in addition to reducing the viability of HUVEC cells. Renal subcapsular inoculation of T24 cells is an interesting model for the study of the formation of new vessels, but animals treated with IDO inhibitor did not shown formation of subcapsular tumor, only infiltrates that not allowed the vascular quantification. The study concludes that IDO is correlated with factors that induce angiogenesis in hypoxic condition and its inhibition decreases the expression of VEGF and viability of endothelial cells. Inhibition of IDO may be a promising alternative for inhibiting angiogenesis in bladder tumors.